RHINO-ORBITO-CEREBRAL MUCORMYCOSIS (ROCM), GRAY AREAS OF MANAGEMENT - A STUDY PRESENTING HIGH INCIDENCE WITH COVID-19 - Shahzadi, Erum; Khalid, Zarnab; Latif, Sarfraz; Qazi, Zia-Us-Salam; Ahmed Malik, Sohail; Ullah, IKram (Journal of Ayub Medical College Abbottabad, 2024)
Background: Rhino-Orbito-Cerebral Mucormycosis is caused by fungi belonging to the Mucorales family, with Rhizopus arrhizus being the most common causative agent. It is a fatal and debilitating condition that is prevalent in developing countries, with a mortality rate ranging from 50% to 85%, reaching 100% in disseminated or untreated cases. The diagnosis is based on tissue histopathology and culture confirmation. Some studies have assessed the efficacy of antifungal regimens. Limited knowledge of the disease, its diverse presentations, delays in early diagnosis, and insufficient efforts to identify the root cause pathogen are key challenges highlighted in the review. Methods: A retrospective study was conducted at Sheikh Zayed Hospital in Lahore, enrolling patients with ROCM from June 2018 to August 2022. Data from patients admitted over five years was collected and analyzed. All patients underwent surgical debridement and received intravenous Amphotericin. A definitive diagnosis was made through microscopic examination of necrotic tissue and cultures. Results: Diabetes mellitus was a common factor among all patients, with a few cases also involving end-stage renal disease and iatrogenic immunosuppression in post-transplant and chemotherapy patients. The study reported a high incidence of ROCM among COVID-19 patients with diabetes mellitus, emphasizing challenges related to treatment costs and patient compliance. Additionally, the one-year survival rate of patients was evaluated. Conclusion: The study concluded that the primary causes of morbidity and mortality included the diversity of disease presentations, missed or delayed diagnoses, inadequate laboratory facilities, high treatment costs, unavailability of antifungal medications, drug toxicity, prolonged hospital stays, and poor follow-up. These issues, along with the emergence of new Mucorales species and drug resistance, underscore the need for focused interventions to address these gray areas.